Eksistensi Ketoprak Panji Anom sebagai Bentuk Pelestarian Budaya Jawa di Desa Kutuk Kecamatan Undaan Kabupaten Kudus - Fita Chusnaya; Luluk Witanti; Khoerul Amin; Adhi Adhani Rizal Ghozali Yatmeidhy; Faisal Nur Faiz; Nadhiya Mauliya Syofa; Aisyah Ayu Maharani; Sefna Yutida Zahra; Chotimah Candra Dewi; Putri Sulistyaningsih; Farelza Septian Ardian Syah; Rossi Galih Kesuma (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia as a country that has many tribes has a culture with the uniqueness of each region. One culture that is still very thick is Javanese culture. Ketoprak as one of the Javanese cultures in the form of drama performances is still often held. Panji Anom is one of the Kutuk Village Ketoprak groups that still preserves the art of Ketoprak by organizing Ketoprak performances when commemorating certain days. As a village that is still thick with culture, Kutuk Village through Ketoprak Panji Anom tries to preserve Javanese culture. Along with the times, traditional culture such as Ketoprak has begun to be unfamiliar among the younger generation. The use of language and storylines that are difficult for the younger generation to understand make Ketoprak no longer relevant as entertainment for young people. The existence of Ketoprak art began to recede among the younger generation, for this reason Ketoprak Panji Anom through creation tried to revive the art of Ketoprak among the younger generation. Ketoprak art, apart from being entertainment, also holds a lot of learning and Javanese advice which is filled with philosophical values.